2016
DOI: 10.3758/s13415-016-0474-8
|View full text |Cite
|
Sign up to set email alerts
|

Perfectionism mediated the relationship between brain structure variation and negative emotion in a nonclinical sample

Abstract: In maladaptive respects, perfectionism reflects an individual's concern over making mistakes and doubting the quality of his or her own actions excessively, which would affect one's emotion. However, little is known about the neural mechanisms associated with the perfectionism and negative affect. In this study, voxel-based morphometry was performed to identify the brain regions underlying individual differences in perfectionism, which was measured by the Chinese Frost Multidimensional Perfectionism Scale (CFM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…Therefore, stressed rescuers with feelings of guilt or failure about their missions are at greater risk of PTSD. Furthermore, biological evidence has shown that perfectionism may be correlated with gray matter volume reduction in the anterior cingulate cortex [35], which is the brain area responsible for emotional regulation and is highly correlated with PTSD [36]. Clinically, rescuers with certain personality tendencies, based on the results of our study, should pay more attention to their psychological condition following rescue missions, and further symptom management can be implemented if the guilty feeling persists.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, stressed rescuers with feelings of guilt or failure about their missions are at greater risk of PTSD. Furthermore, biological evidence has shown that perfectionism may be correlated with gray matter volume reduction in the anterior cingulate cortex [35], which is the brain area responsible for emotional regulation and is highly correlated with PTSD [36]. Clinically, rescuers with certain personality tendencies, based on the results of our study, should pay more attention to their psychological condition following rescue missions, and further symptom management can be implemented if the guilty feeling persists.…”
Section: Discussionmentioning
confidence: 72%
“…Until some decades ago perfectionism was understood as dysfunctional, being related to eating disorders [43,45], anxiety and depression [32], and stress [31,33]. Previous studies starting from this perspective have tried to explain perfectionism without understanding potential factors that can serve as emotional resources to withstand stress [49].…”
Section: Discussionmentioning
confidence: 99%
“…This set of attention regulation strategies is thought to contribute to self-regulation (Rueda et al, 2005), a construct referring to a range of abilities facilitating target-oriented behavior and appropriate reactions to mentally challenging stimuli via control of cognition, emotion, and behavior (Posner et al, 2007;Fjell et al, 2012;Zelazo and Lyons, 2012). Thus, mindfulness training is assumed to foster self-regulation via the improvement of attention regulation.…”
Section: Introductionmentioning
confidence: 99%